(untitled) (Stamford Journal of Microbiology, 2017)
Fruit juices are very popular due to their freshness and taste. These juices contain all the nutritive values those were present in whole fruits. Fresh juices are healthful drink for people of all ages. But the condition is quite opposite if they become contaminated with pathogenic bacteria during the juice processing. Because of the nutritive properties juice can give enough opportunities to the microorganisms to survive and multiply. In our current study we included eight types of fresh juices to study the microbial load. All the samples were heavily contaminated. Total bacterial and fungal count was found to be up to 3.0×107 cfu/ml and 2.6×106 cfu/ml, respectively. Salmonella spp. and Shigella spp. was present only in one sample. Staphylococcus aureus and Pseudomonas spp. were the most prominent in all of the eight samples. Vibrio spp. was found in six samples ranging from 2.0×102 cfu/ml to 2.9×104 cfu/ml. All the pathogenic isolates showed drug resistance towards the most commonly prescribed antibiotics indicating the risk of difficulty in eradicating diseases. Stamford Journal of Microbiology, Vol.6(1) 2016: 7-10